Pengaruh Desain Program dan Pemrograman Web Terhadap Pembuatan E-learning Pada Siswa SMK - Yossi Indrawati Syuhardi (Jurnal Ilmiah Wahana Pendidikan, 2019)
In the fast-paced digital age, effective and practical learning breakthroughs are needed. Learning e learning has penetrated into the world of education. Required mastery of programming design and dynamic web design. The purpose of this study was to determine the effect of program design and web programming on the e learning abilities of vocational students. Respondents were 73 vocational students. The classical test is done by, normality test, multicollinearity, heterosecurity. Then the data is processed with a coofesient table and a summary model. The results showed that there was an effect of Program Design and Web Programming Against the Making of E-learning, there was an influence of design on the making of e learning, and programming to the making of e learning. Students are very enthusiastic and better prepared if they have mastered programming and program design. It is expected that in the future students will be able to continue, adapt to the changing and current programs